Peran Filsafat Ilmu dalam Perkembangan Ilmu Pengetahuan di Era Perkembangan Zaman - Dongoran, Rosita; Salsabila, Nur Ain; Ali, Fatimah; Rahmad, Ambia Perdana (Ikatan Da'i Indonesia, 2024)
This study review saspect sof the philosophy of science that focuses on aspect sof the development of science in the era of the industrial revolution 5.0. The study used a qualitative research method with aliteratur estudy approach.The collection of relevant data information is taken from various library sources suchas;books,journals,news, internet in accordance with the topic of discussion. The results of this study were obtained by classifying the dimensions, elements, and sub-elements of the relationship between philosophy and science, philosophy based on its character and function, the relationship between the philosophy of science and other sciences, studying philosophy, science and the industrial revolution 5.0.